(untitled) (Orfeu, 2025)
The general objective of this article is to analyze the activities of Marcos Leite (1953-2002), pianist, composer and conductor, in the context of counterculture. This is qualitative research based on bibliographic and documental sources that contemplates both the production, circulation and reception of Marcos Leite’s work in the Brazilian scene in the second half of the 20th century, as well as the principles that guided his practice as an arranger, conductor and pedagogue. Initially, we outline an overview of the Brazilian choral movement, from the 1960s onwards, and discuss the work of Marcos Leite in the city of Curitiba. Afterwards, we analyze Vassourinhas(Matias da Rocha and Joana Baptista Ramos), one of his choral arrangements, identifying its formal, harmonic, melodic and rhythmic elements. The results indicate that, alongside other names, Marcos Leite contributed to the aesthetic renewal of choral singing, proposing forms of scenic, visual and gestural performance for singers and conductors.